Beter benutten van kennis uit onderzoek en onderwijspraktijk Kansrijke aanpakken voor docentgroepen - Schenke, Wouter (Kohnstamm Instituut, 2019)
This research was carried out by researchers from the Kohnstamm Institute; this concerns Marianne Boogaard, Irma Heemskerk, Henk Sligte and Wouter Schenke (project leader). They conducted the study together with lecturer researchers working at the consortium schools. Part of the research work was carried out by PhD student Patrick van Schaik, who combines his work as a teacher at one of the consortium schools with doctoral research.